Moisture Optimization and Energy Saving Effects of Combined Organic Acid and Surfactant Inclusion in Pelleted Feed Production - Duygu Budak; Kazım Bilgeçli (Turkish Journal of Agriculture: Food Science and Technology, 2024)
The purpose of the present study was to determine the effects of inclusion of an organic acid and surfactant (OS) combination on moisture optimization and energy sparing in the production of pelleted compound feeds for dairy and beef cattle. The trial was carried out in two independent private commercial feed factories (factories A and B) producing cattle feed in pellet form. Each factory produced 21 tons of commercial cattle feed (7 batches; 3 tons per batch); factory A, a dairy feed containing 2620 kcal/kg metabolizable energy (ME) with 18.90% crude protein (CP); and factory B, a fattening feed containing 2550 kcal/kg ME with 13.00% CP. Batches for the treatment groups were prepared by adding 0.5, 1.0 and 1.5 kg/ton of OS (Fylax flow) respectively to these basal feeds in the mixer. The moisture retention capacity during pelleting process of all three OS supplemented feeds increased in comparison to the basal feed, whilst moisture content of the finished feeds and energy consumed for production decreased significantly. It was observed that increasing the OS supplementation to 1.5 kg could further increase the moisture retention capacity and moisture content in pellet production compared to the feeds supplemented with 0.5 and 1.0 kg OS, due to the lower power rating of the equipment. It has thus been concluded that adding 0.5, 1.0 and 1.5 kg of OS to commercial compound feeds for dairy resulted in a profitable production with good moisture optimization and energy savings during pelleting.